Visuo-Kinetic Signs Are Inherently Metonymic: How Embodied Metonymy Motivates Forms, Functions, and Schematic Patterns in Gesture - Mittelberg, Irene (Frontiers in Psychology, 2019)
TThis paper aims to evidence the inherently metonymic nature of co-speech gestures. Arguing that motivation in gesture involves iconicity (similarity), indexicality (contiguity), and habit (conventionality) to varying degrees, it demonstrates how a set of metonymic principles may lend a certain systematicity to experientially grounded processes of gestural abstraction and enaction. Introducing visuo-kinetic signs as an umbrella term for co-speech gestures and signed languages, the paper shows how a frame-based approach to gesture may integrate different cognitive/functional linguistic and semiotic accounts of metonymy (e.g., experiential domains, frame metonymy, contiguity, and pragmatic inferencing). The guiding assumption is that gestures metonymically profile deeply embodied, routinized aspects of familiar scenes, that is, the motivating context of frames. The discussion shows how gestures may evoke frame structures exhibiting varying degrees of groundedness, complexity, and schematicity: basic physical action and object frames; more complex frames; and highly abstract, complex frame structures. It thereby provides gestural evidence for the idea that metonymy is more basic and more directly experientially grounded than metaphor and thus often feeds into correlated metaphoric processes. Furthermore, the paper offers some initial insights into how metonymy also seems to induce the emergence of schematic patterns in gesture which may result from action-based and discourse-driven processes of habituation and conventionalization. It exemplifies how these forces may engender grammaticalization of a basic physical action into a gestural marker that shows strong metonymic form reduction, decreased transitivity, and interacting pragmatic functions. Finally, addressing basic metonymic operations in signed lexemes elucidates certain similarities regarding sign constitution in gesture and sign. English and German multimodal discourse data as well as German Sign Language (DGS) are drawn upon to illustrate the theoretical points of the paper. Overall, this paper presents a unified account of metonymy’s role in underpinning forms, functions, and patterns in visuo-kinetic signs.